The Role of Communication and Employee Engagement in Promoting Inclusion in the Workplace: A Case Study in the Creative Industry - Afridah; Muhlisah Lubis (Feedback International Journal of Communication, 2024)
This research examines the role of communication and employee engagement in promoting inclusion in the workplace, with a specific focus on the creative industry. The study utilizes a case study approach to gain insights into the strategies and practices employed by organizations in fostering an inclusive work environment. The research objectives are twofold: first, to explore the communication channels and mechanisms utilized by organizations to promote inclusion, and second, to investigate the impact of employee engagement on fostering a culture of inclusion. A mixed-methods approach is employed, combining qualitative interviews with employees and management, as well as quantitative surveys to gather comprehensive data. The findings of the study highlight the crucial role of communication in promoting inclusion. Organizations within the creative industry employ diverse communication channels, such as town hall meetings, intranet platforms, and diversity training programs, to facilitate open dialogue and exchange of ideas. Effective communication practices contribute to enhanced employee understanding, collaboration, and mutual respect, thereby fostering an inclusive work environment. Furthermore, the study reveals that employee engagement plays a pivotal role in promoting inclusion. Engaged employees exhibit higher levels of commitment, motivation, and willingness to embrace diversity. They actively contribute to the creation of an inclusive culture by participating in diversity initiatives, providing feedback, and advocating for inclusive practices. The implications of this research that organizations in the creative industry should prioritize effective communication strategies and employee engagement to foster inclusion. By creating an inclusive work environment, organizations can harness the benefits of diversity, such as increased creativity, innovation, and employee satisfaction.